Investigations on the Association of Mosquito Vector Species with Selected Tree Species in Nigerian Defence Academy, Ribadu Cantonment, Kaduna - Jafaru, Rakiya; Vantsawa, Philip A.; Ajibade, Gabriel A. (Sahel Journal of Life Sciences FUDMA, 2025)
The study aimed to investigate the association of mosquito vector species with selected tree species at the Nigerian Defence Academy Ribadu Cantonment Kaduna. The study design was a Cross-sectional study primarily for distribution and relative abundance assessments. The study was carried out at the Nigerian Defence Academy Ribadu Cantonment, Kaduna, Nigeria. Mosquito samples were collected from the environment of tree species of interest using a mix of methods, as observed from several literatures. These include a yeast and sugar solution trap, a locally constructed hand-net, water-filled containers, and an ovipositing container. Following the mosquito collection on individual trees, physical and molecular identification were done using standard procedures. This was then succeeded by data analysis using Microsoft Excel 2016; descriptive statistics was used for summaries of the data and ANOVA, Chi square test were used to make inferences. A total of 2383 mosquitoes were collected from 140 tree samples of 10 different species. All the tree samples had different numbers of mosquitoes collected, with a variation in species. Terminalia ivorensis had the highest number of mosquitoes (631), and Eucalyptus camaldulensis had the lowest number (74). Using the Shanon Weiner Index calculator, the study was able to analyze the richness and evenness of mosquitoes to trees in the Cantonment. There is a significant relationship between different tree species and mosquito vectors within the Cantonment, and the degree to which mosquitoes are attracted to the tree species is based on specific characteristics of the tree species.